Impact of wind turbulence on thermal perception in the urban microclimate - Yu, Yichen; de Dear, Richard; Chauhan, Kapil; Niu, Jianlei (Journal of wind engineering and industrial aerodynamics, 2021)
Ongoing urbanization has led to complexities in the urban terrain, increasing roughness length within the atmospheric surface layer, and introduced highly turbulent wind flow at pedestrian height. This research aims to explicitly examine the effect of wind flow turbulence on thermal perception under outdoor conditions. A wind tunnel with passive grid was used to introduce turbulence into simulated wind conditions. Thermal physiological (skin temperature) and perceptual (questionnaire) responses were collected from 20 college-age subjects during the exposures to various simulated urban wind conditions. Results confirm that increased turbulence intensity enhances perceived coolness by reducing the skin temperature. We updated the convective heat transfer coefficient in a numerical skin thermoreceptor model and also Gagge's two-node thermophysiological model so that they both reflect more accurately the effects of turbulence intensity on skin temperature. Skin temperatures simulated with the modified models were in good agreement with experimental observations, and corrected the un-modified model's 30% and 50% underestimation of mean skin temperature decrement for standing and cycling conditions respectively. These findings contribute to the broader goal of a thermal comfort model for application to urban microclimate. •The effect of wind flow turbulence on thermal perception under outdoor conditions has been examined though a human subject experiment in the wind tunnel.•The increased turbulence intensity enhances perceived coolness by reducing the skin temperature.•The previously published thermal comfort models may underestimate the mean skin temperature decrement by 30% and 50% for standing and cycling conditions respectively.•Appling a recent manikin-derived convective heat transfer coefficient formula in the existing thermal comfort models can improve the accuracy of the mean skin temperature prediction.